An analysis of deep vein thrombosis in burn patients (Part 1): Comparison of D-dimer and Doppler ultrasound as screening tools. Issue 8 (December 2016) - Ahuja, Rajeev B.; Bansal, Priya; Pradhan, Gaurav S.; Subberwal, Manju
Graphical abstract: Highlights: Compares D-dimer and Doppler ultrasound as screening tools for DVT. 100 adult burn patients, 30–60% TBSA, were studied prospectively. Specificity of D-dimer assay was 20% with a positive predictive value of 5%. Four patients diagnosed with DVT on Doppler ultrasound. All DVTs detected on Doppler ultrasound only. Abstract: Introduction: The high prevalence of deep vein thrombosis (DVT) reported in prospective studies and the unreliability of clinical diagnosis mandates prospective screening for DVT in burn patients. Our study seeks to compare D-dimer and Doppler ultrasound (DUS) in search for a practical, inexpensive and a reliable screening tool. Methods: One hundred burn patients (inclusion criteria: 30–60% TBSA burn, >18 years of age, admitted within 48 h of burn) were computer randomized into two equal groups. The study (prophylaxis) group received low molecular weight heparin (LMWH) (0.5 mg/kg, twice daily-max 60 mg/day) from day one, till discharge. Screening D-dimer assays and DUS of the lower extremities were performed on all 100 patients on day five, and then weekly, till discharge. Results: Signs and symptoms simulating DVT (pain, swelling, redness, warmth, positive Homans' and Moses' sign) were present in majority of patients with lower limb burns. 43/50 patients (86%) in the control group and 38/50 patients (76%) in the study (prophylaxis) group had positive D-dimer values (>0.5 μg/ml) on the 5th post-burn day. D-dimer was positive in all the four patients identified with DVT. However, only 4/100 patients enrolled in the study demonstrated DVT on DUS. Thus, the specificity of the D-dimer assay was only 20% with a positive predictive value of 5%. Absolute D-dimer values were found to have no correlation to the extent of burns. Conclusion: We conclude that D-dimer is not a useful screening tool for DVT in burns contrary to its accepted value in general trauma and medical patients.